PENGARUH ROA, DER, CR DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR RITEL YANG TERDAFTAR DI BEI - Bitasari, Irna; Puspita, Erna; Astuti, Puji (UNIKA Santo Thomas, 2024)
This research aims to determine the effect of Return On Assets, Debt to Equity Ratio, Current Ratio and Sales Growth on Company Value (PBV). This research uses a quantitative causality approach. The data used is secondary data in the form of financial reports of retail sector companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2023 period. The population in the research was 32 companies. The sampling technique used purposive sampling technique, so that 14 companies were obtained as samples. The data analysis technique uses multiple linear regression analysis using IBM SPSS version 25, in the form of classic assumption tests (normality test, multicollinearity test, autocorrelation test, heteroscedasticity test), coefficient of determination test (R²), and hypothesis test (t test and F test) . The results of this research show that partially Return On Assets and Sales Growth have a positive and significant effect on Company Value (PBV), while the Current Ratio and Debt to Equity Ratio have a negative and significant effect on Company Value (PBV). Simultaneously, Return On Assets, Debt to Equity Ratio, Current Ratio and Sales Growth have a significant effect on Company Value (PBV)